A Metal–Organic Framework with Cooperative Phosphines That Permit Post‐Synthetic Installation of Open Metal Sites. Issue 30 (25th June 2018) - Dunning, Samuel G.; Nandra, Gianne; Conn, Adam D.; Chai, Wenrui; Sikma, R. Eric; Lee, Ji Sun; Kunal, Pranaw; Reynolds, Joseph E.; Chang, Jong‐San; Steiner, Alexander; Henkelman, Graeme; Humphrey, Simon M.
Abstract: PCM‐101 is a phosphine coordination material comprised of tris(p‐carboxylato)triphenylphosphine and secondary pillaring groups coordinated to [M3 (OH)] 5+ nodes (M=Co, Ni). PCM‐101 has a unique topology in which R3 P: sites are arranged directly trans to one another, with a P⋅⋅⋅P separation distance dictated by the pillars. Post‐synthetic coordination of soft metals to the P: sites proceeds at room temperature to provide X‐ray quality crystals that permit full structural resolution. Addition of AuCl groups forces a large distortion of the parent framework. In contrast, CuBr undergoes insertion directly between the trans‐P sites to form dimers that mimic solution‐phase complexes, but that are geometrically strained due to steric pressure exerted by the MOF scaffold. The metalated materials are active in heterogeneous hydroaddition catalysis under mild conditions, yielding different major products compared to their molecular counterparts. Abstract : Trans ‐phosphines in a MOF : A phosphine‐containing coordination material, PCM‐101, is the first example of a trans ‐phosphine binding pocket within a MOF. Single‐crystal‐to‐single‐crystal metal addition allows for incorporation of strained versions of analogous small‐molecule trans ‐phosphine complexes.